2021
DOI: 10.35877/soshum485
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Traditional Practices and Gender-Based Violence

Abstract: This study assessed if traditional practices such as early marriage, Female genital cutting and honour violence perpetuate gender-based violence in Obudu Local Government Area of Cross River State, Nigeria. The study adopted the quasi-experimental research design in selecting four hundred samples from Obudu Local Government Area using stratified and purposive sampling technique. The questionnaire and interview guide were the instruments used for data collection. Quantitative data collected was analyzed using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In Nigeria, the case is not different, the National Population Commission and ICF international report in 2017 estimate that women exposed to intimate violence from their intimate partner stand at 19 per cent for intimate emotional violence, 14 per cent for intimate physical violence and 5 per cent for sexual intimate violence (NPC & ICF, 2017; Benebo, 88 Schumann, & Vaezghasemi, 2018;Ojong-Ejoh, Cobham, Iloeje, & Tangban, 2021). Other studies in Nigeria on intimate partner violence revealed that 31 to 61 per cent suffer from sexual violence and 7 to 31 per cent from physical violence (Barebo, Schuman & vaezghasemi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, the case is not different, the National Population Commission and ICF international report in 2017 estimate that women exposed to intimate violence from their intimate partner stand at 19 per cent for intimate emotional violence, 14 per cent for intimate physical violence and 5 per cent for sexual intimate violence (NPC & ICF, 2017; Benebo, 88 Schumann, & Vaezghasemi, 2018;Ojong-Ejoh, Cobham, Iloeje, & Tangban, 2021). Other studies in Nigeria on intimate partner violence revealed that 31 to 61 per cent suffer from sexual violence and 7 to 31 per cent from physical violence (Barebo, Schuman & vaezghasemi, 2018).…”
Section: Introductionmentioning
confidence: 99%